Taxonomic studies in the Macrolobium campestre complex (Leguminosae) - Félix-Da-Silva, Maria Maricélia; Bastos, Maria De Nazaré Do Carmo; Gurgel, Ely Simone Cajueiro (Phytotaxa, 2016)
Macrolobium is a neotropical genus with approximately 80 species distributed from Central to South America. In Brazil, the upper Rio Negro basin in Amazonia is the center of diversity for the genus. A taxonomic study based on the type materials and additional specimens of M. campestre deposited in several herbaria was carried out. The results show that the taxonomic diversity at the infraspecific level has been overestimated. Thus this work proposes synonymizing Macrolobium campestre var. arirambense R.S. Cowan, M. campestre var. arboreum R.S. Cowan, M. campestre var. longibracteatum R.S. Cowan and M. campestre var. medium R.S. Cowan under Macrolobium campestre Huber.